On Rabbits, Rats, and Low-Hanging Fruit: Rethinking the Impact of International Agreements On China’s Domestic Cultural Property Protection - Marton, Autumn L. (Columbia Journal of Asian Law, 2009)
By the light of the burning palace which had been the pride and delight of her Emperors, she had commenced to see that she had been asleep while all the world was up and doing . . .. The Sum- mer Palace with all its wealth of art, was a high price to pay for the lesson we there received, but not too high, if it has taught us how to repair and triple fortify our battered armour; and it has done so. -Marquis Tseng1 On February 23, 2009, Christie’s began the three-day auction of the personal collection of fashion designer Yves Saint Laurent and his partner, Pierre Berg6. Realizing 6374 million ($474 million) in total sales,2 the auction benefited a new HIV/AIDS research institute.3 Breaking the world record for the highest single-owner sale of art on the first night alone,4 onlookers commented that bidders were behaving as if they were “dancing on the Titanic,”5 paying unprecedented prices for works ranging from highly regarded paintings by Mondrian and Matisse to whimsical pieces such as Eileen Gray’s “Dragons” armchair and Marcel Duchamp’s readymade toilet water flasks.6 The auction represented to some an indi- cation of a “separate trajectory” for the art market from the increasingly depressed world economy,7 and to others the natural recognition that Berg6 and Saint Laurent shared a “discerning eye for provenance and mu- seum quality.”8 [1] As cited in CARROLL BROWN MALONE, HISTORY OF THE PEKING SUMMER PALACES UNDER THE CH’ING DYNASTY 192 (1934). [2] Auction Results, Christie’s, Collection Yves Saint Laurent et Pierre Berg6, Sept. 26, 2008, http://www.christies.com/LotFinder/searchresults.aspx?intSalelD=22294#action=refine&intSalelD =22294&sid=a0322868-0bd4-4d94-92b6-48bfe I 2f6b5a. [3] Press Release, Christie’s, The Yves Saint Laurent and Pierre Berg6 Collection, Sept. 26, 2008, http://www.christies.com/presscenter/pdf/09262008/12319.pdf (last visited May 22, 2009). [4] Souren Melikian, Paris Auction Reflects a Major Turning Point for Art Market, INT’L HERALD TRIB., Feb. 28, 2009, at 14. [5] Katharine Zaleski, Yves Saint Laurent Auction: Record Brancusi, Matisse, Mondrian Sales, HUFFINGTON POST, Feb. 23, 2009, http://www.huffingtonpost.com/2009/02/23/yves-saint-laurent- auctio n 16920 1.html. [6] See Souren Melikian, Yves Saint Laurent Art Sells for 6206 Million, INT’L. HERALD TRIB., Feb. 25, 2009, at 9. [7] Melikian, supra note 4. [8] Artdaily.org, The Collection of Yves Saint Laurent and Pierre Berg6 Realises $483.8 Million at Christie’s, http://www.artdaily.org/index.asp?int-sec=2&int new-29281 (last visited May 22, 2009).